2015
DOI: 10.14260/jemds/2015/331
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of External and Endonasal Dacryocysto - Rhinostomy in Acquired Nasolacrimal Duct Obstruction

Abstract: AIM:To compare the success rate and complications of external dacrycystorhinostomy with that of endonasal dacryocystorhinostomy. STUDY DESIGN: Prospective randomized comparative study. MATERIAL AND METHODS: Sample Size: The study comprises of 60 eyes of 54 consecutive patients with chronic dacryocystitis of which 28 patients underwent external dacryocystorhinostomy and 26 patients underwent endonasal endoscopic dacryocystorhinostomy. All the patients were selected by simple random method. INCLUSION CRITERIA: A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
1
0
Order By: Relevance
“…In terms of success rate, previous studies have shown a higher rate of success of external DCR than endoscopic DCR. In the prospective randomized comparative study of Nailwal et al [ 18 ], the overall success rate of external dacryocystorhinostomy after three months of surgery was 93.33%, whereas that of endonasal dacryocystorhinostomy was 90%, but this difference was not statistically significant (p=1.0). Dasgupta et al [ 19 ] reported the same findings, with an overall success rate of 92.80% for DCR surgery.…”
Section: Reviewmentioning
confidence: 99%
“…In terms of success rate, previous studies have shown a higher rate of success of external DCR than endoscopic DCR. In the prospective randomized comparative study of Nailwal et al [ 18 ], the overall success rate of external dacryocystorhinostomy after three months of surgery was 93.33%, whereas that of endonasal dacryocystorhinostomy was 90%, but this difference was not statistically significant (p=1.0). Dasgupta et al [ 19 ] reported the same findings, with an overall success rate of 92.80% for DCR surgery.…”
Section: Reviewmentioning
confidence: 99%
“…It may result from a wide variety of causes, the commonest cause is nasolacrimal duct obstruction (NLDO) (2) , which may be congenital or acquired. Acquired NLDO may be primary or secondary (3) .…”
Section: Introductionmentioning
confidence: 99%